A Suction-Powered Elastic-Strap Gripping Device (International Journal of Innovative Research in Engineering & Management, 2023)
"In recent decades, there has been an  increasing need for robotic gripping device capable of  sensitively handling things of varied forms. While classic  finger-shaped gripping devices are adaptable and can grab  a broad variety of things, achieving a firm hold without  slippage demands precise alignment of the fingers on the  object. This study offers the notion of a ring-like delicate  gripper that wraps across items much resembles an elastic  string. The implied gripper is constructed of a flexible  tube having layers of sponges interspersed with plastic  sheets. By emptying the air inside the sponges, they  contract, lowering the ring's diameter and permitting a  tight grasp on things. This endows the gripper with the  flexibility to wrap around items of varied forms  flawlessly, leaving no opportunity for gaps. Moreover,  the hardness of the compressed sponges inside the gripper  mitigates any possible swaying of the grabbed items.  Airborne particles inside The device that grips may be  modified to fine-tune the grabbing energy. After air is  emptied from the sponges, the gripper's minimal diameter  is roughly one-fourth of its initial size. Consequently, our  suggested gripper is set to find applications across a range  of sectors, giving the potential to simply and firmly hold  things while seamlessly adjusting to their various forms."
Keywords: Soft Gripper; Robotic Handling; Object Manipulation; Gripping Technology; Flexible Automation